Nurses' potentialities and difficulties in identifying clinical deterioration (Revista Contexto & Saúde, 2026)
Objective: to analyze the strengths and challenges faced by nurses in identifying clinical deterioration in adult patients in a general medicine unit. Methods: a qualitative and descriptive study conducted at a university hospital in southern Brazil between March and June 2024. Sixteen nurses, selected through purposive sampling, participated. The data for this article were collected through participant observation and semi-structured interviews and analyzed using discursive textual analysis with the aid of IRAMUTEQ software. Results: The strengths identified included effective communication among the nursing team, the use of handover tools, early detection of clinical changes, and teamwork. The difficulties, on the other hand, were related to the absence of care protocols, structural and logistical limitations, a diverse patient population, high staff turnover and professional inexperience, failures in interprofessional communication, and demotivation at work. Conclusion: The identification of clinical deterioration is influenced by organizational and communication factors, as well as by nurses’ professional experience, highlighting the need for institutional strategies that strengthen patient safety.
Keywords: Clinical Deterioration; Nursing Care; Hospital Care; Communication